Pseudomonas allii sp. nov., a pathogen causing soft rot of onion in Japan. Issue 1 (3rd January 2021) - Sawada, Hiroyuki; Fujikawa, Takashi; Tsuji, Mizue; Satou, Mamoru
Abstract : Six phytopathogenic bacterial strains, MAFF 301512, MAFF 301513, MAFF 301514 T, MAFF 301515, MAFF 301516 and MAFF 301517, were isolated from soft rot lesions of onion ( Allium cepa L.) in Japan. The cells were Gram-reaction-negative, aerobic, non-spore-forming, motile with one or two polar flagella and rod-shaped. Analysis of their 16S rRNA gene sequences showed that they belong to the genus Pseudomonas, with the highest similarities to Pseudomonas poae DSM 14936 T (99.86 %), Pseudomonas simiae OLi T (99.85 %), Pseudomonas trivialis DSM 14937 T (99.79 %) and Pseudomonas extremorientalis KMM 3447 T (99.79 %). Their genomic DNA G+C content was 60.9 mol% and the major fatty acids (>5 % of the total fatty acids) present were C16 : 0, summed feature 3 (C16 : 1  ω7 c /C16 : 1  ω6 c ), summed feature 8 (C18 : 1  ω7 c /C18 : 1  ω6 c ) and C17 : 0 cyclo. Phylogenetic and phylogenomic analyses based on the rpoD gene and whole genome sequences, respectively, demonstrated that the strains belong to the Pseudomonas fluorescens subgroup, but form a monophyletic and robust clade, with Pseudomonas azotoformans as their neighbour. Between the strains and P. azotoformans, the average nucleotide identity scores were 95.63–95.70 %, whereas the digital DNA–DNA hybridization scores of the strains against their closest relatives, including P. azotoformans, were 65.4 % or less, which are lower than the 70 % cut-off for prokaryotic species delineation. The strains were differentiated from their closest relatives by phenotypic characteristics, pathogenicity in onion and cellular fatty acid composition. The phenotypic, chemotaxonomic and genotypic data showed that the strains represent a novel Pseudomonas species, proposed to be named Pseudomonas allii sp. nov., with MAFF 301514 T (=ICMP 23680 T ) being the type strain.